(untitled) (Bangladesh Critical Care Journal, 2020)
First reported in Wuhan, China, SARS-COVID 19 infection is now fairly well described but understanding the disease is evolving and is associated with high incidence of fatal pneumonia. However, concomitant vascular thromboembolism is also being recognized as contributing to mortality and severe morbidity. We report limb salvage in a COVID-19 patient despite presenting late with critical limb ischaemia and radiological evidence of embolism in multiple organs. Bangladesh Crit Care J September 2020; 8(2): 124-125